(untitled) (Archaeologia Adriatica, 2008)
Legionary denarii are Roman Republican coins emitted from mobile military mints under the control of various military commanders. In the Republican period, coins were emitted from the central mint of the city of Rome, but amidst the frequent war operations and internal conflicts during the first century BC, coinage was also minted in other places, particularly where the armies were located, as this enabled carrying out payments in the shortest possible time to military units throughout the even then enormous state. This article is concerned with the legionary denarii of Marcus Antonius with the typical depiction of a warship on the obverse. Although several types of coins of Marcus Antonius are known, the frequency of finds of the above type indicates that it played a significant role in the monetary circulation in the last decades of the first century BC. This type was minted in enormous quantities, and with its distribution Marcus Antonius, the powerful oligarch and ruler of the eastern part of the Roman state, was able to ensure regular payments to the soldiers of his legions, and by this act also their loyalty. Although Octavianus delivered a decisive blow against him in the battle at Actium in 31 BC, his legionary denarii still remained in circulation. Hoard finds even show that they remained sporadically in circulation to the end of the second, and even to the beginning of the third century. It is generally accepted today that this type of legionary denarius was minted in 32-31 BC, but other opinions have also been expressed. The most interesting conjecture is that of M. Chitescu, who considered that they were emitted by the mint of Ephesus from 39 BC all the way to the battle of Actium. In the region of northern Dalmatia, the legionary denarii of Marcus Antonius have been noted at 12 sites, which includes two hoard finds. It is certain that part of them arrived in this area with the Roman army in the last decades of the 1st century BC and the beginning of the 1st century AD. However, because of the fact that they remained in circulation for even more than two centuries, only for examples from hoards such as those found below Cvijina gradina and at Nin can we be more or less certain when they were deposited in the earth.